1999
DOI: 10.1021/jf981211e
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoretic Determination of Resveratrol in Wines

Abstract: A rapid and sensitive capillary electrophoretic method for analysis of resveratrol in wine was established. The protocol consists of sample preparation using a C-18 solid-phase extraction cartridge. Baseline separation of trans- and cis-resveratrol from other compounds in wine was achieved in approximately 8 min using a micellar mode. The limits of detection for trans- and cis-resveratrol were 0.1 and 0.15 micromol/L, respectively. Recovery rates for trans-resveratrol using the protocol described ranged from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 25 publications
3
59
2
1
Order By: Relevance
“…Resveratrol was well-tolerated and no severe adverse reactions were reported in the two studies. In addition, the present study investigated the doses of resveratrol used in various in vivo and in vitro studies, as well as the concentration required to elicit noteworthy pharmacological activities (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)22,23). In vitro data showed that a minimum of 5 µmol/l resveratrol is required for the chemopreventive effects to be elicited (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resveratrol was well-tolerated and no severe adverse reactions were reported in the two studies. In addition, the present study investigated the doses of resveratrol used in various in vivo and in vitro studies, as well as the concentration required to elicit noteworthy pharmacological activities (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)22,23). In vitro data showed that a minimum of 5 µmol/l resveratrol is required for the chemopreventive effects to be elicited (15).…”
Section: Discussionmentioning
confidence: 99%
“…The trans form is able to undergo isomerization into the cis form upon exposure to ultraviolet irradiation (9). Although the two isomers often exist in combination, the trans form is more biologically active and more frequently investigated (8,9,17,18). Red wine is known to contain a high concentration of trans-resveratrol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key polyphenol in red wine is resveratrol, trans-3,5,4Ј-trihydroxystilbene, from grape skin. Red wine contains 1-75 mg of transresveratrol/liter (3). Studies in male rats demonstrated that an alcohol-free red wine extract and resveratrol protect the heart from ischemia reperfusion injury (4).…”
mentioning
confidence: 99%
“…These results were later improved by the use of a solid phase extraction step previous to the determination by MEKC [71]. In this case, limits of detection of 0.1 and 0.15 μM for trans and cis resveratrol, respectively, were reached.…”
Section: Resveratrolmentioning
confidence: 99%